Joggle lap shear testing of deep occlusal composite restorations lined with Dycal, Dycal LC, conventional or resin-modified glass ionomer - Stojanovska, Vera; Ivanoff, Chris S; Muratovska, Ilijana; Popovska, Lidija; Garcia-Godoy, Franklin; Hottel, Timothy L.; Marković, Dejan LJ.; Morrow, Brian (Vojnosanitetski pregled, 2017)
Background/Aim. The longevity of a dental restoration may be predicted to some degree by its adhesive ability, and this, in turn, can be measured by bond strength testing between restorative materials and tooth structure. The aim of this study was to test an innovative joggle lap shearing jig that integrates the tooth and the entire biomechanical unit into testing, to compare the shear bond strengths of Class I occlusal composite restorations in deep cavity preparations lined with Dycal, Dycal LC, conventional glass ionomer or resin-modified glass ionomer. The mode of failure (adhesive, cohesive, mixed) after debonding was determined by stereomicroscopy. Methods. A total of 150 standardized occlusal cavities were prepared and divided into five groups. The group I cavities (n = 30) were coated with adhesive (ExciTE®F) and filled directly with composite (TetricEvoCeram). The group II and III cavities were lined with Dycal (n = 30) or Dycal LC (n = 30) before placing composite. The groups IV and V specimens were based with Fuji IX (n = 30) or Fuji II LC (n = 30). Shear bond strengths were determined with a universal testing machine and fractured bonding sites were analyzed under stereomicroscope. The mean bond strengths were analyzed using one-way ANOVA test (p < 0.05) and the means between the groups were analyzed with Student’s t-test. Results. The shear bond strength (MPa) of composite restorations in cavities without base (23.91 ± 4.54) was higher than cavities lined with Fuji II LC (17.45 ± 2.74), Fuji IX (8.76 ± 2.57), Dycal LC (13.07 ± 1.84) or Dycal (6.12 ± 1.28). The results using the jogged lap shearing jig were consistent with the literature. Conclusion. The shear bond strength of occlusal composite restorations in deep cavities without liners was greater than cavities lined with Fuji II LC > Fuji IX > Dycal LC > Dycal.
Keywords: biomechanics; dentin-bonding agents; adhesives; dental cements; calcium hydroxide; materials testing; in vitro